Fothergilla major Large Fothergilla, Mountain Witchalder: FPS-215/FP215, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the Fothergilla major, commonly known as large fothergilla or mountain witchalder. It describes the shrub’s physical characteristics, including its height, spread, and seasonal changes in foliage and flowers. The document also outlines the plant’s growing conditions, such as soil preferences, light requirements, and drought tolerance. Additionally, it highlights the plant’s uses in landscaping, noting its ornamental features and suitability for various planting locations. The document emphasizes the plant’s low pest resistance and the importance of minimal pruning to maintain its natural form.